We vs. them: Perception of terrorism in multiethnic Bosnia and Herzegovina in an intergroup perspective - Lalić, Velibor (International journal of law, crime and justice, 2025)
This study explores how intergroup bias and conflict can be reduced in multiethnic Bosnia and Herzegovina, fostering conditions for intergroup dialogue that could lead to more effective counterterrorism policies. Intergroup Emotions Theory (IET) was applied to examine differences in perceptions of terrorism (PTQ-SF) based on ethnic/religious affiliation and sex. MANCOVA revealed statistically significant differences in perceptions of terrorism among ethnic groups of Bosnia and Herzegovina within the convenience sample (N = 576), with four out of eight subscales showing such differences. Additionally, significant differences were found between women and men across four subscales. Importantly, it was observed that sex, through re-categorization as a common category overlapping with ethnicity, may help reduce interethnic animosity by "reconciling" perceptions of terrorism. The theoretical and practical implications of these findings are discussed.